2013
DOI: 10.1038/onc.2013.259
|View full text |Cite
|
Sign up to set email alerts
|

Self-reinforcing loop of amphiregulin and Y-box binding protein-1 contributes to poor outcomes in ovarian cancer

Abstract: The Y-box binding protein-1 (YB-1) transcription factor is associated with unfavorable clinical outcomes. However, the mechanisms underlying this association remain to be fully elucidated. We demonstrate that YB-1 phosphorylation, indicative of YB-1 activation, is a powerful marker of outcomes for ovarian cancer patients. In ovarian cancer, YB-1 phosphorylation is induced by activation of the lysophosphatidic acid (LPA) receptor (LPAR) via SRC-dependent transactivation of the epidermal growth factor receptor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 53 publications
(66 reference statements)
2
33
0
Order By: Relevance
“…It was suggested that nuclear translocation of YBX1 could induce upregulation of EGFR expression and a more aggressive NSCLC phenotype (56). A recent report further revealed YBX1 as a convergent hub for lysophosphatidic acid and EGF signaling, and activation of YBX1 contributed to ovarian cancer cell invasion (57). Considering the multifaceted roles of C1QBP and YBX1, together with our observation that they present as "hubs" within the CHCHD2 interactome, we propose that CHCHD2 functions, at least in part, through interactions with C1QBP and YBX1.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that nuclear translocation of YBX1 could induce upregulation of EGFR expression and a more aggressive NSCLC phenotype (56). A recent report further revealed YBX1 as a convergent hub for lysophosphatidic acid and EGF signaling, and activation of YBX1 contributed to ovarian cancer cell invasion (57). Considering the multifaceted roles of C1QBP and YBX1, together with our observation that they present as "hubs" within the CHCHD2 interactome, we propose that CHCHD2 functions, at least in part, through interactions with C1QBP and YBX1.…”
Section: Discussionmentioning
confidence: 99%
“…The ultimate goal in the fi eld is to generate a new class of anticancer molecules that either alone or in combination with traditional chemotherapeutics can complement the apoptosis in ovarian cancer cells ( 112 ). Several known signaling networks implicated in ovarian cancer progression, including the Hippo-YAP axis ( 155 ), the amphiregulin/Y-box binding protein-1 positive feed-back loop ( 156 ), and EGFR signaling ( 157 ), have been shown to be regulated through LPA signaling, likely in coordination with ATX activity.…”
Section: Role In Physiology and Cancer Pathophysiologymentioning
confidence: 99%
“…The biological actions of LPA are mediated via at least six different receptors (LPA [1][2][3][4][5][6] belonging to the Gprotein-coupled receptor (GPCR) family [1,3,6,7]. Strong evidence implicates LPA in malignancy [1,4,[8][9][10][11] and indicates a role in the development, progression, and invasiveness of various cancers, such as carcinomas of the ovary, prostate, breast, thyroid, liver, head and neck, and gastrointestinal tract [4,9,[11][12][13][14][15][16][17][18][19][20]. Both autotaxin and LPA receptors have been proposed as potential targets for anticancer therapy [1,21,22].…”
Section: Introductionmentioning
confidence: 99%